Implementation of Management Functions in Educational Institutions - Sholichah, Umi; Ahal , Royanah (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2024)
Management functions are the basic elements that will always exist and are inherent in the management process that will be used as a reference by managers in carrying out activities to achieve goals. Management functions were first introduced by a French industrialist named Henry Fayol in the 20th century. The management functions of Islamic education in the review of the Qur'an are divided into: 1) Planning, 2) Organizing, 3) Mobilizing, 4) Evaluation (Control). Good planning, efficient organizing, effective direction, and careful control are important elements in the management of educational institutions. By implementing these management functions properly, educational institutions can provide quality education and make a positive contribution to the development of society and individuals. In implementing management functions, educational institutions can ensure that their operations run efficiently and effectively to achieve quality educational goals.